Analysis of the Use of Indonesian Affixes in WhatsApp Status - Ilmatus Sa'diyah; Danella Dhariyanto; Yulia Rahma Rahma Auliya; Haikal Akbar Maulana (MEDIASI : Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2023)
This research aims to explain the form and meaning of affixes or affix terms in WhatsApp application status. This type of research is descriptive research by collecting data through the screenshot technique on the WhatsApp status that appears through the researcher's status column. The researcher analyzes the affixes contained therein using descriptive analysis techniques and classifies the affixes based on their type. According to the results of the research that has been done, it can be concluded that the form and meaning of Indonesian affixes in WhatsApp status are found, including; (a) prefixes include {meN-}, {ber-}, {di-}, {ter-}, {se-}; (b) the infix includes {-em-}; (c) suffixes include {-an}, {-i}, {-kan}, and {-nya}; (d) confixes include {ke-...-an}, {pen-...- an}, and {per-...an} ; (e) simulfix includes {re-...-kan}, {receive-....-i}, {me-...i-}, {me-...-kan}, and {di-. ..-i}. The results of this research are expected to provide a lot of information to the public regarding the use of affixes.